Insight into the Covalently Oriented Immobilization of Antibodies on Gold Nanoparticle Probes to Improve Sensitivity in the Colorimetric Detection of Listeria monocytogenes - Sawinee Ngernpimai; Sukanya Srijampa; Patsara Thongmee; Saowapak Teerasong; Theerapong Puangmali; Wanchai Maleewong; Apiwat Chompoosor; Patcharaporn Tippayawat (Bioconjugate Chemistry, 2022)
for food safety and in other applications.
Keywords: Biosensors and Analytical Detection; Gold and Silver Nanoparticles Synthesis and Applications; Advanced biosensing and bioanalysis techniques